Analysis of international practice of wholesale distribution centers formation and development - O. V. Kotova (Путеводитель предпринимателя)
The article presents the results of the analysis of the international practices of the formation and development of the wholesale distribution centers, the actual formation problems of the Russian wholesale distribution centers.